Analysis of the gut contents of culion silverside, Atherinomorus regina (Seale, 1909) in Conception, Iloilo - Dionaldo, Leanna N.; Campos, Wilfredo (2016.)
This study was conducted to examine the gut contents of Atherinomorus reginausing specimens from push net catches sampled in December 2011 to January 2012 in Plandico, Concepcion, Iloilo. One hundred fish specimens were categorized into seven different size classes maintaining an interval of 0.5cm: 1.5-1.9cm, 2.0-2.4cm, 2.5-2.9cm, 3.0-3.4cm, 3.5-3.9cm, 4.0-4.4cm, 4.5-4.9cm. The guts of these fishes were isolated and contents were flush out to a petri dish for identification and counting. The results showed variation in the percent chyme and non-chyme component. The chyme component was inversely related to fish size, and decreased as the size of fish increased. Also, food items were more diverse in large fishes as compared to the smaller fishes. Atherinomorus regina, primarily feed on diatoms, fish eggs and larvae, and also on copepods. They can be considered as generalists by having a wide range of prey items, especially in the larger size classes.
Special Problem -- Bachelor of Science in Biology. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Gut Content; Gut-content Analysis; Athernomorus regina; Prey items